1977
DOI: 10.1083/jcb.73.1.200
|View full text |Cite
|
Sign up to set email alerts
|

Continued initiation of DNA synthesis in arginine-deprived Chinese hamster ovary cells.

Abstract: When exponentially growing CHO cells were deprived of arginine (Arg), cell multiplication ceased after 12 h, but initiation of DNA synthesis continued: after 48 h of starvation with continuous [3H]thymidine exposure,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In contrast, the susceptible tumour cell line, HeLa, continues to enter S-phase and traverse the cycle, albeit slowly. In agreement with Weissfeld and Rouse [8][9][10], synchronised HeLa cells took an inordinately long time to attain near G2 complements of DNA when released into S-phase in the absence of arginine ( Fig. 9a and b).…”
Section: Arginine Deprivation Cell Cycle Progression and Deathsupporting
confidence: 65%
See 1 more Smart Citation
“…In contrast, the susceptible tumour cell line, HeLa, continues to enter S-phase and traverse the cycle, albeit slowly. In agreement with Weissfeld and Rouse [8][9][10], synchronised HeLa cells took an inordinately long time to attain near G2 complements of DNA when released into S-phase in the absence of arginine ( Fig. 9a and b).…”
Section: Arginine Deprivation Cell Cycle Progression and Deathsupporting
confidence: 65%
“…Responses of human diploid fibroblasts, which have stringent regulation at the restriction point in G1 [6] , have been compared with HeLa cells. In contrast to isoleucine deprivation in CHO cells, which causes a G1 arrest [7], Weissfeld and Rouse [8][9][10] showed that KB cells continued to enter S-phase in arginine deficient medium. They paid little attention to effects beyond 48 h of total deprivation, and drew no comparisons with "normal" cells.…”
Section: Introductionmentioning
confidence: 99%
“…Arginine is consumed at a relatively high rate by CHO cells in antibody production processes . Arginine starvation can cause CHO cells in exponential phase to be captured in the G0 or G1 phase . Excess arginine in the culture medium can effectively reduce the ratio of the acidic species of products.…”
Section: Key Components Of Mammalian Cell Culture Mediamentioning
confidence: 99%
“…81 Arginine starvation can cause CHO cells in exponential phase to be captured in the G0 or G1 phase. 82 Excess arginine in the culture medium can effectively reduce the ratio of the acidic species of products. However, unlike lysine, high arginine concentrations can inhibit cell growth and reduce viability.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Deprivation of single amino acids including arginine induces severe chromosome abnormalities in cultured cells (Freed & Schatz, 1969). Growth inhibition by arginine depletion is associated with continued initiation of DNA synthesis (Weissfeld & Rouse, 1977) but severely depressed protein and RNA synthesis (Weinberg & Becker, 1970). This type of metabolic imbalance (although the other way round) is reminiscent of the effect of thymidine excess on cultured cells, which also causes severe chromosome damage (Yang et al, 1966) and is selectively cytotoxic for malignant cells (Lee et al, 1977).…”
Section: Effect Of Complete Arginine Deprivation On Cell Numbersmentioning
confidence: 99%